2003
DOI: 10.1002/j.1467-8438.2003.tb01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Tape Measures in Family Therapy: An Exploration of the Global Assessment of Relational Functioning

Abstract: In the current climate of evidence-based clinical practice, there is an urgent need to give family therapy research more prominence, and to demystify it for the practitioner. We were curious to discover how a family assessment instrument would behave with families we saw in our clinical practice. This paper describes our first attempt to apply a family measure, the Global Assessment of Relational Functioning, with 51 families in which the referred child presented with a confirmed or suspected diagnosis of AD/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Reliability has been evaluated by comparing ratings made by different raters of the same family therapy sessions. Inter-rater reliability has ranged from .54 when comparing intake session ratings made by graduate student therapists and their faculty supervisors (Rosen, McCollum, Middleton, Locke, & Bird, 1997), to .62 for a therapist and co-therapist ⁄ observer rating an intake session (Stiefel, Johnson, Clarke, & Chahoud, 2003), to .72 for raters viewing video recordings of a structured family task (Dausch, Miklowitz, & Richards, 1996), to .75 for trainees rating a clinical intake session (Wilkins & White, 2001). Hay, Katsikitis, Begg, Da Costa, and Blumenfeld (2003) reported a strong intraclass correlation of .98 between two raters who conducted 12 joint interviews.…”
mentioning
confidence: 99%
“…Reliability has been evaluated by comparing ratings made by different raters of the same family therapy sessions. Inter-rater reliability has ranged from .54 when comparing intake session ratings made by graduate student therapists and their faculty supervisors (Rosen, McCollum, Middleton, Locke, & Bird, 1997), to .62 for a therapist and co-therapist ⁄ observer rating an intake session (Stiefel, Johnson, Clarke, & Chahoud, 2003), to .72 for raters viewing video recordings of a structured family task (Dausch, Miklowitz, & Richards, 1996), to .75 for trainees rating a clinical intake session (Wilkins & White, 2001). Hay, Katsikitis, Begg, Da Costa, and Blumenfeld (2003) reported a strong intraclass correlation of .98 between two raters who conducted 12 joint interviews.…”
mentioning
confidence: 99%
“…Anecdotal evidence suggests that the GARF received little use by family therapists or other mental health practitioners. This is unfortunate as research has consistently demonstrated the GARF's reliability and validity (e.g., Dausch, Miklowitz & Richards, ; Denton, Nakonezny & Burwell, ; Stein, Hilsenroth, Pinsker‐Aspen & Primavera, ; Stiefel, Johnson, Clarke & Chahoud, ). At this writing, it is not known whether the GARF will be retained in DSM‐5 but given the elimination of the multiaxial system, it would seem there may not be a place for it.…”
Section: Implications Of Dsm‐5 For Family Therapistsmentioning
confidence: 99%
“…Family assessment. Stiefel et al (2003) argued for the routine assessment of families before and after treatment with the Global Assessment of Relations Functioning Scale (GARF) to evaluate treatment effectiveness. The GARF, a simple, reliable rating scale, is included in an appendix of DSM IV TR (APA, 2000).…”
Section: Therapy Process Researchmentioning
confidence: 99%